Viability Evaluation of Domestic Solar Hot Water Systems using two Multi Criteria Evaluation Techniques: Case Study of an Urban Area in India - Srinivas, Morapakala (Journal of Technology Innovations in Renewable Energy, 2013)
Despite the proven favourable techno-economic feasibilities along with the organised promotional measures, solar hot water systems are not diffused to the extent they should be, even in the domestic front of urban India where the potential for such dissemination is high. The reasons for such a low dissemination of domestic solar hot water systems (DSHWS) could be due to multi-criteria covering various dimensions of viability of domestic water heating options. This paper presents the work taken up to study the viability of DSHWS vis-à-vis other competing water heating options, on multi-criteria covering technical, economic, commercial, social and behavioural dimension in the urban India context, with a special reference to Bangalore. The strengths and weaknesses, significant dimensions and criteria for better dissemination of DSHWS vis-à-vis other competing water heating options, as obtained from the analysis using two multi criteria evaluation techniques viz. PROMETHEE and AHP are presented.